3D screening device for the evaluation of cell response to different electrospun microtopographies. (June 2017) - Criscenti, G.; Vasilevich, A.; Longoni, A.; De Maria, C.; van Blitterswijk, C.A.; Truckenmuller, R.; Vozzi, G.; De Boer, J.; Moroni, L.
Graphical abstract: Abstract: Micro- and nano-topographies of scaffold surfaces play a pivotal role in tissue engineering applications, influencing cell behavior such as adhesion, orientation, alignment, morphology and proliferation. In this study, a novel microfabrication method based on the combination of soft-lithography and electrospinning for the production of micro-patterned electrospun scaffolds was proposed. Subsequently, a 3D screening device for electrospun meshes with different micro-topographies was designed, fabricated and biologically validated. Results indicated that the use of defined patterns could induce specific morphological variations in human mesenchymal stem cell cytoskeletal organization, which could be related to differential activity of signaling pathways. Statement of Significance: We introduce a novel and time saving method to fabricate 3D micropatterns with controlled micro-architectures on electrospun meshes using a custom made collector and a PDMS mold with the desired topography. A possible application of this fabrication technique is represented by a 3D screening system for patterned electrospun meshes that allows the screening of different scaffold/electrospun parameters on cell activity. In addition, what we have developed in this study could be modularly applied to existing platforms. Considering the different patterned geometries, the cell morphological data indicated a change in the cytoskeletal organization with a close correspondence to the patterns, as shown by phenoplot and boxplot analysis, and might hint at the differential activity of cell signaling. The 3D screening system proposed in this study could be used to evaluate topographies favoring cell alignment, proliferation and functional performance, and has the potential to be upscaled for high-throughput.